Low Nitrogen Application Enhances Starch-Metabolizing Enzyme Activity and Improves Accumulation and Translocation of Non-structural Carbohydrates in Rice Stems - Li, Guohui; Hu, Qiuqian; Shi, Yange; Cui, Kehui; Nie, Lixiao; Huang, Jianliang; Peng, Shaobing (Frontiers in Plant Science, 2018)
More than 4 billion inhabitants in Asia depend on rice for 35%-60% of the calories consumed in their diets, but new rice cultivars frequently do not reach expected yields because of poor rice grain filling. Here, we quantified the activities of enzymes involved in starch metabolization in rice to investigate the mechanisms regulating the accumulation and translocation of stem non-structural carbohydrates (NSC) under different levels of nitrogen fertilizer application. A pot experiment was conducted using two rice cultivars, Liangyoupeijiu (LYPJ) and Shanyou63 (SY63), under high and low nitrogen applications. Compared with high nitrogen application (HN), low nitrogen application (LN) increased stem NSC concentration before the heading stage and NSC translocation during the grain filling stage; concomitantly, LN significantly shortened the active grain filling period and increased the grain filling rate in superior spikelets. Compared with the LYPJ cultivar, SY63 exhibited a higher grain weight, higher grain filling percentage, and higher stem NSC concentration before heading and greater NSC translocation after heading. During the period between panicle initiation and heading, the activities of adenosine diphosphate-glucose pyrophosphorylase (AGP), starch synthase (StS), and starch branching enzyme (SBE), all enzymes involved in starch synthesis, increased under the LN treatment and positively correlated with increases in stem NSC. During grain filling, the activities of enzymes involved in starch-to-sucrose conversion (α-amylase, β-amylase, and sucrose phosphate synthase) increased under the LN treatment and positively correlated with stem NSC remobilization. Overall, the investigated enzymes exhibited higher activities in SY63 than in LYPJ. Our results suggest that low nitrogen increases the activities of AGP, StS, SBE, α-amylase, β-amylase, and SPS, leading to increased accumulation and remobilization of stem starch and NSC in SY63. We conclude that calculated reductions in nitrogen application and the choice of an appropriate cultivar may improve rice grain yields via enhanced stem NSC accumulation and translocation, thereby reducing the costs and increasing the sustainability of rice production.